1999
DOI: 10.1002/(sici)1099-1050(199903)8:2<165::aid-hec423>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Health knowledge and smoking among South African women

Abstract: While several studies of developed countries have attempted to understand individual smoking using economic models, no such studies have been conducted in South Africa. The purpose of this paper is to identify which factors influence individual South African women's choice to smoke cigarettes and their knowledge of the health risks of smoking. To allow for the implied correlation between the unobservable components of the reduced form equations for these health inputs the model is estimated as a bivariate prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This was based on the hypothesis that having a good knowledge of the harmful health consequences of VD could help women decide not to douche. Several health belief models suggest that health risk perception could enhance behavioral modification to reduce lifestyle-related risk (Kenkel, 1991;Hseih et al, 1996;Jones and Kirigia, 1999;Kan and Tsai, 2004). In Viscusi 1991, reported that smokers are less likely to smoke as their subjective risk for dying of lung cancer increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was based on the hypothesis that having a good knowledge of the harmful health consequences of VD could help women decide not to douche. Several health belief models suggest that health risk perception could enhance behavioral modification to reduce lifestyle-related risk (Kenkel, 1991;Hseih et al, 1996;Jones and Kirigia, 1999;Kan and Tsai, 2004). In Viscusi 1991, reported that smokers are less likely to smoke as their subjective risk for dying of lung cancer increases.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reproductive outcomes associated with VD include preterm delivery, low birth weight, ectopic pregnancy and infertility (Kenkel, 1991;Martino and Vermund, 2002). These negative health effects have been shown to be exacerbated by an increased frequency of douching (Hseih et al, 1996;Jones and Kirigia, 1999). Despite the numerous adverse health effects of VD in women, there are generally no public health programs to educate the populace, especially those at a higher risk of practicing douching (that is, the less educated, women with low socio-economic status, young, black, unmarried and urban dwellers).…”
Section: Introductionmentioning
confidence: 99%
“…The study finds that the more smoking-related diseases that an individual knows, the less likely he/she is to smoke. Hsieh et al (1996), based on data from Taiwan, and Jones and Kirigia (1999), based on a sample of South African women, show similar findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Demand analysis is widely used to explain use of addictive substances [13,14], contraceptives [15], toilets [16] and human organs. Informed use of these methods can greatly enhance targeting of health-related interventions geared at modifying human behaviour, including sexual habits that expose individuals to a high risk of HIV infection.…”
Section: Health and Health Indices (Figure 1: Box A And B)mentioning
confidence: 63%